New records of Rhagoletis (Diptera: Tephritidae) in Colombia, with discussion on the morphological variations of some species - Martínez-Alava, Javier O.; Serna, Francisco; Norrbom, Allen L. (Zootaxa, 2017)
Rhagoletis jamaicensis Foote, 1981 and an undetermined species of the psalida group, are recorded for the first time in Colombia. The morphological variations of the Colombian specimens of these species and of other species closely related are discussed.